1998
DOI: 10.1073/pnas.95.5.2406
|View full text |Cite
|
Sign up to set email alerts
|

SHOT, a SHOX-related homeobox gene, is implicated in craniofacial, brain, heart, and limb development

Abstract: Deletion of the SHOX region on the human sex chromosomes has been shown to result in idiopathic short stature and proposed to play a role in the short stature associated with Turner syndrome. We have identified a human paired-related homeobox gene, SHOT, by virtue of its homology to the human SHOX and mouse OG-12 genes. Two different isoforms were isolated, SHOTa and SHOTb, which have identical homeodomains and share a C-terminal 14-amino acid residue motif characteristic for craniofacially expressed homeodoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
113
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 37 publications
4
113
0
1
Order By: Relevance
“…4D). The similar situation was also observed for the expression of SHOX2, a member of the short stature homeobox gene family (Blaschke et al, 1998;Semina et al, 1998). In the developing mouse tooth, Shox2 expression is restricted to the dental epithelium from the early bud stage to the cap stage ( Fig.…”
Section: Expression Of Fgf8 Pax9 and Shox2 In Developing Human Tootsupporting
confidence: 72%
“…4D). The similar situation was also observed for the expression of SHOX2, a member of the short stature homeobox gene family (Blaschke et al, 1998;Semina et al, 1998). In the developing mouse tooth, Shox2 expression is restricted to the dental epithelium from the early bud stage to the cap stage ( Fig.…”
Section: Expression Of Fgf8 Pax9 and Shox2 In Developing Human Tootsupporting
confidence: 72%
“…In mouse, only one Shox family member, Shox-2, has been identified to date Cobb et al, 2006). The amino acid sequences between human and mouse Shox-2 proteins are 99% identical (Blaschke et al, 1998;Semina et al, 1998). Unlike SHOX, the association of SHOX-2 gene with human disease has not been reported.…”
mentioning
confidence: 99%
“…The founding member of this family, human SHOX gene, is associated with bone related short-stature disorders including Turner syndrome and Leri-Weill syndromes (Clement-Jones et al, 2000). Human SHOX2 gene shares 80% similarity with human SHOX gene at amino acid level in the homeodomain and C-terminal regions (Blaschke et al, 1998;Semina et al, 1998). In mouse, only one Shox family member, Shox-2, has been identified to date Cobb et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there are genes exhibiting multiple functions at different stages of development or in different tissues and cell types. Blaschke et al (1998) have identified a human paired-related homeobox gene, SHOT, which is implicated in craniofacial, brain, heart, and limb development. Merlo et al (2000) have reported that DIx genes, comprising a highly conserved family of homeobox genes, are expressed in spatially and temporally restricted patterns in craniofacial primordia, basala telencephalon, and diencephalon, and in distal regions of extending appendages, including the limb and the genital bud; these genes seem to have multiple functions at different stages of development or in different tissues and cell types.…”
mentioning
confidence: 99%